PERTUMBUHAN SETEK JAMBU AIR (Syzygium aqueum Burm.) ‘CITRA’ PADA BERBAGAI SUMBER AUKSIN - Meilani, Rizka Fatika; Rahayu, Arifah; Mulyaningsih, Yanyan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Water guava (Syzygium aqueum Burm.) ‘Citra’ is one of Indonesia's native fruits that is much in demand by the public because of its crispy flesh, sweet taste, high water content, high economic value, and has no seeds. Efforts to maintain the superior nature of these plants can be done by vegetative propagation, among others by cuttings. Efforts to increase the success of cuttings can be done using auxin with the right concentration to induce root growth. This study aims to determine the growth of water guava (Syzygium aqueum Burm.) ‘Citra’ cuttings on various auxin sources. The research was conducted from March 2024 to May 2024 at the Experimental Garden of IPB Tropical Horticulture Study Center, South Bogor District, West Java. This study used a completely randomized design (CRD) with a single factor consisting of six levels, namely control, 1000 ppm IBA, 1000 ppm NAA, a combination of 1000 ppm IBA + 1000 ppm NAA, 200 ppm Rootone-F, and 50% shallot extract. The results showed that the 50% shallot extract treatment was the best in shoot emergence time, number of shoots, shoot length, and number of leaves, but not significantly different from the 200 ppm Rootone-F treatment. The best 1000 ppm IBA + 1000 ppm NAA treatment on the most roots.